The Relationship Between Education Level and Population Structure on Labor Absorption in Gorontalo Province - Novriansyah, Moh Arif; Mopangga, Herwin; Yakup, Anggita Permata (AIBPM Publisher, 2025)
This study aims to analyze the influence of Educational Attainment and Population Structure on Labor Absorption in Gorontalo Province. A quantitative approach was employed using multiple linear regression analysis with secondary data derived from nine observations, covering variables such as education level, demographic structure, and labor absorption. The results indicate that both Educational Attainment and Population Structure have a positive and statistically significant impact on labor absorption, both partially and simultaneously. The regression model shows an R² value of 0.855, indicating that 85.5% of the variation in labor absorption can be explained by the two independent variables. These findings suggest that improving the quality of education and effectively managing the productive-age population are key factors in enhancing regional labor absorption. The study concludes that integrated policies between the education and employment sectors, along with optimal utilization of demographic bonuses, are essential. It is recommended that local governments focus on increasing the competence of the workforce through education aligned with labor market needs, and expanding inclusive and sustainable employment opportunities.